Schärfe der optischen Obergrenze der Ozonschicht - Stille, Ulrich (Vieweg, 1952)
A difference [delta]x of the heights in the atmosphere of the earth is considered as a measure of the 'sharpness' of the optical upper limit of the ozone-layer which strongly absorbs ultraviolet sunlight in the spectral region of the Hartley-band. This difference [delta]x is defined by the condition that an ultraviolet sunbeam, traversing the atmosphere at the height x* with the intensity I0 ([lambda]), by the absorption of the ozone will be weakened to an intensity I([lambda])=lO^-2.I0([lambda]) if the path of the sunbeam through the atmosphere is lowered by the amount of [delta]x. Approximating the real distribution of atmospheric ozone with height by suitable exponential functions, the constants of which are to be taken from the observed distributions, the thickness d of absorption in the ozone-layer is evaluated for different basic heights x0 of the ultraviolet beam. In this way, using different decadic coefficients of absorption, [alpha]([lambda]), of the Hartley-band, one gets the corresponding curves of I([lambda])/I0([lambda]) against the height h aver the ground for the average distributions of atmospheric ozone over Arosa and Tromso. From a detailed discussion of these curves, it follows that the 'sharpness' [delta]x of the optical upper limit of the atmospheric ozone-layer is of the order of 1 to 2 km. The consequences for the decay with time of the intensity of the D-lines of sodium, emitted in the twilight, are mentioned.